The Effectiveness Of Group Counseling With A Motivational Interviewing Technique To Improve The Self-Compassion Of Students Victims Of Bullying - Fauzi, Ikhwan; Sugiharto, DYP; Formen, Ali (Universitas Negeri Semarang, 2022)
Self-compassion helps protect an individual from self-evaluation anxiety when considering personal weaknesses. The increase in self-compassion is associated with the increase in mental health of students victims of bullying. Based on this background, the present study aimed at determining the effectiveness of group counseling using a motivational interviewing technique to increase self-compassion of students victims of bullying in grade ten at SMA Negeri 1 Subah. It was an experimental research which used a single group pretest-multiple posttest design. As many as 6 tenth graders were selected through purposive sampling from 69 students. Findings indicated that the motivational interviewing technique was effective in increasing self-compassion in students victims of bullying in grade ten at SMA Negeri 1 Subah. This finding can an implication for designing guidance and counseling services for students victims of bullying.